Spatial range, temporal span, and promiscuity of CLE-RLK signaling - Narasimhan, Madhumitha; Simon, Rüdiger (Frontiers in Plant Science, 2022)
CLAVATA3/EMBRYO SURROUNDING REGION-RELATED (CLE) signaling through receptor-like kinases (RLKs) regulates developmental transitions and responses to biotic and abiotic inputs by communicating the physiological state of cells and tissues. CLE peptides have varying signaling ranges, which can be defined as the distance between the source, i.e., the cells or tissue that secrete the peptide, and their destination, i.e., cells or tissue where the RLKs that bind the peptide and/or respond are expressed. Case-by-case analysis substantiates that CLE signaling is predominantly autocrine or paracrine, and rarely endocrine. Furthermore, upon CLE reception, the ensuing signaling responses extend from cellular to tissue, organ and whole organism level as the downstream signal gets amplified. CLE-RLK mediated effects on tissue proliferation and differentiation, or on subsequent primordia and organ development have been widely studied. However, studying how CLE-RLK regulates different stages of proliferation and differentiation at cellular level can offer additional insights into these processes. Noteworthy, CLE-RLK signaling also mediates diverse non-developmental effects, which are less often observed; however, this could be due to biased experimental approaches. In general, CLEs and RLKs, owing to the sequence or structural similarity, are prone to promiscuous interactions at least under experimental conditions in which they are studied. Importantly, there are regulatory mechanisms that suppress CLE-RLK cross talk in vivo, thereby eliminating the pressure for co-evolving binding specificity. Alternatively, promiscuity in signaling may also offer evolutionary advantages and enable different CLEs to work in combination to activate or switch off different RLK signaling pathways.